(untitled) (Journal of the College of Basic Education, 2024)
Depression is one of the psychological problems that individuals face to a large extent in different environments, and it is of great importance in the studies that are widely conducted, whether in diagnosing it, preventing its infection, treating it, or building effective tools and measures that detect it. Psychiatry believes that depression is a condition Moods with special symptoms appear in the form of mental disorders that can be diagnosed with depression tests. The World Health Organization expects a steady increase in the rates of depression in future generations. The conditions of the environmental factor directly affect the learner or the individual in a society, and the difficulty of the school curricula also affects the learners and causes some They suffer from depression due to failure to take into account individual differences and the difficulty of the subject that exceeds the learner’s age group in the basic education stage and its various curricula, including mathematics in general and the first three stages of primary education for mathematics in particular. The reason for this may also be due to the teacher’s lack of knowledge and familiarity with everything. What is new in teaching methods and then using them to present mathematical content? On the one hand, the teacher’s inability to present mathematical content in a simple and desirable way to learners in the first three stages of primary education, despite his understanding of his specialty or the subject of mathematics, is considered the first problem that causes depression among learners. Which reflects negatively on the learner and the educational process with the emergence of new problems. The research aims to find out the causes of psychological depression related to mathematical content among basic education students in Maysan Governorate. The current study adopted the descriptive approach - survey studies, and the current study reached results, conclusions and recommendations